Aprendizaje de las matemáticas: conceptos, procedimientos, lecciones y resolución de problemas (ING) - Ruiz, Ángel (2003)
We analyze the main objectives for the development of a mathematics lesson, clarifying conceptual and procedural knowledge and their association to different visions about mathematics and its nature. We strongly support the relevance of the conceptual and abstract dimensions of mathematical instruction based on an appropriate pedagogical and cultural framework. The use of a problem solving strategy is strongly supported, and in this context we summarize some aspects of the Japanese experience.